2015
DOI: 10.1259/bjr.20140552
|View full text |Cite
|
Sign up to set email alerts
|

The utility of MRI for pre-operative T and N staging of gastric carcinoma: a systematic review and meta-analysis

Abstract: Objective: To perform a meta-analysis and literature review regarding the diagnostic accuracy of MRI for pre-operative tumour depth invasion (T) and regional lymph node invasion (N) staging of gastric carcinoma (GC). Methods: Articles were identified through systematic search of Medline, PubMed, Cochrane Library, Web of Science, Springerlink and several Chinese databases. The study quality was assessed by the quality assessment for studies of diagnostic accuracy. 2 reviewers independently extracted and assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 33 publications
0
29
0
1
Order By: Relevance
“…The evidence for the use of DW-MRI alone in cancer diagnosis is overwhelming with nearly 1000 publications and numerous meta-analyses in the last decade advocating its use in a variety of tumor types. 98101 Diagnostic accuracies vary by disease site, but in most meta-analyses, sensitivity and specificity were greater than 80%, except for prostate cancer, wherein pooled sensitivity for DW-MRI in a meta-analysis of 21 studies was 62% 102 and in breast cancer wherein specificity at best is around 71%. 103 In both these tumor types, therefore, there has been a move to use a combination of parameters to improve diagnostic performance and an increasing body of data are accruing indicating the superiority of a multi- over a single parameter approach (Fig.…”
Section: Value Of Mpmri In Clinical Decision-makingmentioning
confidence: 98%
“…The evidence for the use of DW-MRI alone in cancer diagnosis is overwhelming with nearly 1000 publications and numerous meta-analyses in the last decade advocating its use in a variety of tumor types. 98101 Diagnostic accuracies vary by disease site, but in most meta-analyses, sensitivity and specificity were greater than 80%, except for prostate cancer, wherein pooled sensitivity for DW-MRI in a meta-analysis of 21 studies was 62% 102 and in breast cancer wherein specificity at best is around 71%. 103 In both these tumor types, therefore, there has been a move to use a combination of parameters to improve diagnostic performance and an increasing body of data are accruing indicating the superiority of a multi- over a single parameter approach (Fig.…”
Section: Value Of Mpmri In Clinical Decision-makingmentioning
confidence: 98%
“…However, when compared to other standard techniques like CT or EUS, no benefit or even inferior results were seen regarding the accuracy of lymph node assessment (32,33). One recent comparative study and a recent meta-analysis concluded that MRI was a helpful technique in staging the T-category and had a poor detection rate for lymph node metastasis in gastric cancer (34,35). MRI, when used in a liver-specific protocol, is mostly used to clarify suspicious liver lesions if no biopsy is performed (16).…”
Section: Magnetic Resonance Imaging (Mri)mentioning
confidence: 99%
“…Yayımlanan bir meta analizde MR görüntülemenin T1-2 ile T3-4 tümörlerin ayrımında yüksek tanısal doğruluk gösterdiği; nodal evrelemede ise duyarlılığı yüksek olsa da özgüllüğünün düşük olduğu gösterilmiştir (88). Özellikle difüzyon ağırlıklı görüntülemenin T evrelemesinin doğruluğunu artırdığı, Borrmann tip 4 ileri mide kanserinin yeterince şişirilmemiş normal mide duvarından ayrımına katkı sunduğu belirtilmektedir (86).…”
Section: öZofagusvemidekanserlerindepet/mrunclassified